Evaluation of Biochemical, Haematological, and Histopathological Responses and Recovery Ability of Common Carp (Cyprinus carpio L.) after Acute Exposure to Atrazine Herbicide. (27th March 2014) - Blahova, Jana; Modra, Helena; Sevcikova, Marie; Marsalek, Petr; Zelnickova, Lenka; Skoric, Misa; Svobodova, Zdenka
Abstract : The aim of study was to evaluate the effect of atrazine exposure (5, 15, 20, and 30 mg·L −1 ) on common carp and the ability of regeneration. During 96 h exposure we observed abnormal behavior in fish exposed to 20 and 30 mg·L −1 . Mortality and histological alterations were noticed only in the group exposed to 30 mg·L −1 . Most experimental groups showed significantly (P < 0.05 ) lower values of haemoglobin, haematocrit, leukocyte, and lymphocyte and significantly higher values of monocytes, segmented and band neutrophile granulocytes, and also metamyelocytes and myelocytes. A significantly lower (P < 0.05 ) leukocyte count was also recorded in experimental groups (5 and 15 mg·L −1 ) after recovery period. Statistically significant (P < 0.05 ) alterations in glucose, total protein, lactate, phosphorus, calcium, and biopterin as well as in activities of ALT, AST, ALP, and LDH were found in most experimental groups. These changes were most apparent in the groups exposed to 20 and 30 mg·L −1 . Most of the indices were found to be restored after the 7-day recovery period with the exception of LDH, ALT, and lactate in the group exposed to 15 mg·L −1 . Our results showed that atrazine exposure had a profound negative influence on selected indices and also on histological changes of common carp.